On the Efficiency of the Multi-Channel Analysis of Surface Wave Method for Shallow and Semi-Deep Loose Soil Layers - Kasgin Khaheshi Banab; Dariush Motazedian (International Journal of Geophysics)
The multi-channel analysis of surface waves (MASWs) method was used to obtain the shear wave velocity variations through near surface (depth < 30 m) and semi-deep (30 m < depth < 100 m) soil layers in the city of Ottawa, Canada. Sixteen sites were examined to evaluate the capability of the active and passive MASW methods for cases where the shear wave velocity (Vs) contrast between very loose soil (Vs < 200 m/s) and very firm bedrock (Vs > 2,300 m/s) is very large. The MASW velocity results compared with those of other geophysical approaches, such as seismic reflection/refraction methods and borehole data, where available, mostly confirming the capability of the MASW method to distinguish the high shear wave velocity contrast in the study area. We have found that, of the inversion procedures of MASW data, the random search inversion technique provides better results than the analytical generalized inversion method.